2021
DOI: 10.1108/ijoa-03-2021-2684
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial finance and crowdfunding in the Middle East

Abstract: Purpose The purpose of this study is to analyze crowdfunding (CF) as new entrepreneurial finance (EF) tool and to predict the success of CF projects in the Middle East region. Design/methodology/approach This study was conducted in seven Middle Eastern countries (i.e. Turkey, Egypt, Iraq, Saudi Arabia, Bahrain, Kuwait and UAE) in addition to serval CF platforms that are commonly used by crowd funders in this region (such as Kickstarter, GoFundMe, Beehive and Zoomal) with total members (195,193). A pilot samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 57 publications
2
16
0
Order By: Relevance
“…Moreover, this is on the right path towards maximizing resources through the home office. These findings are similar and consistent with studies developed by [21,122,158]. In this same direction, the study carried out by Nofiani et al [159] shows that SMEs are currently in a state plagued by uncertainty and must adapt to market situations and internal needs.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, this is on the right path towards maximizing resources through the home office. These findings are similar and consistent with studies developed by [21,122,158]. In this same direction, the study carried out by Nofiani et al [159] shows that SMEs are currently in a state plagued by uncertainty and must adapt to market situations and internal needs.…”
Section: Discussionsupporting
confidence: 91%
“…Accordingly, we sought to examine the perceptions of young entrepreneurs (qualified students) in Saudi Arabia concerning the use of crowdfunding platforms to finance their small enterprises. This is because it has been reported that crowdfunding platforms are a useful financial technology for supporting Middle Eastern start-ups (Abdeldayem & Aldulaimi, 2021). Furthermore, the concept of crowdfunding is linked to Fintech, which has exploded in popularity, affecting every aspect of the financial system.…”
Section: Introductionmentioning
confidence: 99%
“…It is noticed that such a venture can appear as “equity purchase, loan, donation, or preordering of the product” proposing various types of crowdfunding. 29 Another clarification states crowdfunding to be another technique for financing, in light of a mediator (platform), which joins sponsor/financial backers, who are conventional individuals able to put limited quantities into great undertakings, to entrepreneurs, which normally address valiant groundbreaking thoughts and have issues with pulling in account utilizing different channels. 30…”
Section: Literature Reviewmentioning
confidence: 99%